Liquidity risk management : practice among Croatian firms - Karanović, Goran, ekonomist (Array, 2018)
The main purpose of this paper is to explore the practice of liquidity risk management of Croatian business entities. The analysis is based on a survey of 62 business entities in Croatia. The authors investigate the existence of risk management and liquidity risk management measures among the surveyed business entities. The respondents’ knowledge of management, their use of indicators and methods for the management of liquidity risk, in addition to the cited reasons for implementation of liquidity risk measures were also subject to examination. Furthermore, the authors investigate the importance of liquidity management in business. The analysis reveals that Croatian business entities have neither sufficient knowledge regarding the majority of financial indicators, nor they tend to use liquidity management plans. Consequently, the survey’s findings indicate that the overall level of financial knowledge of Croatian managers is inadequate. This can, thus, be identified as one of the reasons for the traditionally high number of illiquid business entities in the market. Finally, this paper provides academia and policymakers with new revelations concerning the management of liquidity risk among business entities in Croatia.